Interrelationship of Mathematical Problem-Solving Ability, Mathematical Disposition, and Gender among Grade 10 Students - Tampa, Alimuddin; Ihsan, Hisyam; Sulleng, Ofra Maylin (UNNES JOURNAL, 2024)
Although numerous studies have examined mathematical disposition (MD) and mathematical problem-solving (MPS) ability, a significant gap remains in understanding their interaction with gender differences. This study aimed to analyze the effect of MD on MPS, investigate gender-based differences, and identify the most influential MD indicators. Conducted in South Sulawesi, Indonesia, this research involved 300 tenth-grade students using an ex-post facto quantitative design. The instruments comprised a mathematical problem-solving test and a mathematical disposition questionnaire. Data were analyzed using descriptive and inferential statistics. The findings indicated that 77.6% of students were classified as having low MD, while 71.0% exhibited similarly low levels of MPS. MD significantly affected MPS (59.5%), with the indicator 'appreciation of the value of mathematics' making the largest contribution (0.293). Significant gender differences emerged in MD, whereas no such differences were observed in MPS. These findings highlight the importance of innovative and differentiated teaching strategies that prioritize improving students’ MD. Such strategies are essential for fostering inclusive, responsive, and equity-oriented mathematics education, a commitment that educators and policymakers should actively strive to uphold. Meskipun banyak penelitian telah mengeksplorasi disposisi matematis (DM) dan kemampuan pemecahan masalah matematika (MPS), kesenjangan signifikan masih ada dalam memahami interaksinya dengan perbedaan gender. Penelitian ini bertujuan untuk menganalisis pengaruh DM terhadap MPS, mengeksplorasi perbedaan berdasarkan gender, serta mengidentifikasi indikator DM yang paling berpengaruh. Penelitian ini melibatkan 300 siswa kelas sepuluh di Sulawesi Selatan, Indonesia, dengan desain kuantitatif ex-post facto. Instrumen penelitian meliputi tes kemampuan pemecahan masalah matematika dan angket disposisi matematis. Data dianalisis menggunakan statistik deskriptif dan inferensial. Hasil menunjukkan 77.6% siswa berada dalam kategori rendah pada DM, sementara 71.0% menunjukkan tingkat MPS yang serupa. DM memberikan kontribusi signifikan terhadap MPS (59.5%), dengan indikator 'apresiasi terhadap nilai matematika' memberikan kontribusi terbesar (0.293). Terdapat perbedaan signifikan pada DM berdasarkan gender, namun tidak pada MPS. Temuan ini menyoroti pentingnya strategi pengajaran yang inovatif dan berbeda yang memprioritaskan peningkatan MD siswa. Strategi semacam itu sangat penting untuk mendorong pendidikan matematika yang inklusif, responsif, dan berorientasi pada kesetaraan, sebuah komitmen yang harus ditegakkan oleh para pendidik dan pembuat kebijakan secara aktif.